Hidden Foreign Body in the Orbit and Cavernous Sinus Masquerading Strabismus - Rauniyar, RK; Badhu, B; Sharma, U; Panda, A (Nepalese Journal of Radiology, 2012)
Intraorbital foreign bodies with intracranial extension can produce both visual and life threatening problems. The present report highlights a 9 year old patient who sustained an ocular trauma following a fall from a height, but refused to admit the same and reported to the ophthalmologist late when complicated symptoms such as deviation of eye ball with mild proptosis appeared. The authors described the value of accurate history taking and complete radiological evaluation for these traumatised eyes. Clinical examination and routine radiological study may not be sufficient to detect these foreign bodies. DOI: http://dx.doi.org/10.3126/njr.v1i1.6323 Nepalese Journal of Radiology Vol.1(1): 41-44